Psychopathy : antisocial, criminal, and violent behavior - Millon, Theodore (New York ; London : Guilford, 1998)
I: History and viewpoints * Historical conceptions of psychopathy in the United States and Europe / Theodore Millon, Erik Simonsen and Morten Birket-Smith
* Psychopathy: An elusive concept with moral overtones / John Gunn
* Personality and crime / H. J. Eysenck
* Psychopathy and the contribution of personality to violence / Ronald Blackburn
* Evil intent: Violence and disorders of the will / Henry Richards
* The internal world of the psychopath / J. Reid Meloy and Carl B. Gacano
* Antisocial character and behavior: Threats and solutions / William H. Reid
* The case for parental licensure / David T. Lykken
* Psychopathy or antisocial personality in forensic settings / Hans Toch
II: Typologies
* Ten subtypes of psychopathy / Theodore Millon and Roger D. Davis
* Psychopathy and the five-factor model of personality / Thomas A. Widiger and Donald R. Lynam
* Psychopaths and their nature: Implications for the mental health and criminal justice systems / Robert D. Hare
III: Etiology
* Genetics and antisocial personality disorder / Peter McGuffin and Anita Thapur
* Neurobiology in psychopathy / Larry J. Siever
* Psychopathic children: Indicators of organic dysfunction / Niels Peter Rygaard
* Cross-cultural aspects of psychopathy / David J. Cooke
* A biopsychosocial model of psychopathy / Joel Paris
IV: Comorbidity
* Psychopathy and psychiatric comorbidity / Alv A. Dahl
* Psychopathy in the pedophile / Darwin Dorr
* Comorbidity of alcoholism and psychopathy / Joachim Knop, Per Jensen and Erik Lykke Mortensen
* Antisocial personality disorder and narcotic addiction / Per Vaglum
* Sadistic personality in murderers / Michael H. Stone
V: Treatment
* Psychopharmacological treatment and impulsivity / Lars von Knorring and Lisa Ekselius
* The psychotherapeutic management of psychopathic, narcissistic, and paranoid transferences / Otto F. Kernberg
* A group-analytic approach to psychopaths: "The Ring of Truth" / Murray Cox
* Therapeutic community treatment for severe personality disorders / Bridget Dolan
* The management of dangerous psychopaths in prison / Jeremy W. Coid
* Treating the "untreatable" in Denmark: Past and present / Heidi Hansen
Bibliografija iza svakog poglavlja
Kazalo
Keywords: psihopatija; antisocijalno ponašanje; kriminalno ponašanje; nasilničko ponašanje